2016
DOI: 10.1002/erv.2463
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Risk and Disordered Eating: Decreased R Wave Amplitude in Women with Bulimia Nervosa and Women with Subclinical Binge/Purge Symptoms

Abstract: The purpose of the present study was threefold. First, we examined whether women with bulimia nervosa (n = 12) and women with subthreshold binge/purge symptoms (n = 20) showed decreased mean R wave amplitude, an indicator of cardiac risk, on electrocardiograph compared to asymptomatic women (n = 20). Second, we examined whether this marker was pervasive across experimental paradigms, including before and after sympathetic challenge tasks. Third, we investigated behavioural predictors of this marker, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…19 Women with an altered R-wave amplitude in the study were more likely to have sudden ventricular arrhythmias. 19 However, not all studies support an acute association of bulimia with changes in the myocardium. A recent study in Denmark of 531 women with bulimia and 125 women without found no evidence of an association of bulimia with QT prolongation or with immediate cardiac events and all-cause mortality.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…19 Women with an altered R-wave amplitude in the study were more likely to have sudden ventricular arrhythmias. 19 However, not all studies support an acute association of bulimia with changes in the myocardium. A recent study in Denmark of 531 women with bulimia and 125 women without found no evidence of an association of bulimia with QT prolongation or with immediate cardiac events and all-cause mortality.…”
Section: Discussionmentioning
confidence: 83%
“…1 Electrical conduction defects in bulimia coincide with electrolyte imbalance and hypokalemia. [19][20][21] In women diagnosed with severe bulimia and hypokalemia, QT interval prolongation and repolarization abnormalities may lead to sudden acute ventricular arrhythmias and death. 21 A study of 52 women diagnosed with bulimia in the United States who binged and purged found a lower R-wave amplitude on the electrocardiogram, indicating reduced cardiac contractile force and signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Binge episodes characteristically involve highly processed foods and contain an average of 2415 kcal per episode [ 63 ]. The prevalence of hypercholesterolaemia is increased among women with BN (estimates range from 19 to 48%) and it is thought that the binge-restrict cycle is responsible for this derangement which represents a major risk factor for cardiovascular disease [ 64 , 65 ].…”
Section: Cardiovascular Complications In Other Eating Disorders: Buli...mentioning
confidence: 99%